El rendimiento de las secretarias y su incidencia en la ejecución de los procesos administrativos - Mora Uriarte, Miriam Marisela (2019)
The present work of investigation to allowed collect information for the development of this case, through different activities, it was obtained various methods those that were essential for the purpose of this work, mention is made below of the diverse processes that were applied; the inductive method was used, descriptive the investigation, field and bibliographic, because these helped to verify directly, the most important aspects and relevant to the problem raised, which allowed to carry out, the analysis of the negative situation, within the institution, the technique was also applied as is the interview and as an instrument the questionnaire, the one that led to evidence the results, through the criteria of each of the determining factors in the realization of this case, and those who were validated by the different opinions of the interviewees. To detail the development of the case, the use of a number of aspects is mentioned, those who allowed the completion of each of these activities, the detected situations were found, through interviews, with which a series of irregularities could be analyzed in each situation, and which allowed to reach the conclusions of the problem of this investigation and similarly develop the solutions proposed, the recommendations and suggestions based on the subject of study